Tratamiento del defecto epitelial persistente basado en suero alogénico: Presentación de caso. (2024)
An observational and experimental clinical case report was carried out in which the allogeneic serum from a donor (niece of the patient) who accepted and signed consent informed for participation in the study, serological tests were subsequently requested with favorable results for obtaining and preparing allogeneic serum.